The Integrative Approach to the Concepts of Business Strategy - Tamaševičius, Virginijus (Ekonomika, 1996)
The aim of business strategy is to find a fit between a company and its environment. Several explanatory ideas can be used to create the basis of the theory explaining the interaction of companies and their environment. These ideas can be grouped according to two main criteria: the priority they give to outside or inside forces in determining the actual strategy of a company, and the priority they give to subjective/ cognitive or objective/ analytical ways of the strategy’s development. Four concepts of business strategy based on different assumptions have been discussed: the classical theory of the strategy, the company’s competencies theory, the network theory, and the learning organization theory. Four different approaches in analysing strategy can not be taken separately as just alternative theories. It is better to say, they constitute complementary pans of one very complex process of realisation of the strategy by a company. The approaches discussed were developed by western scholars and they generalise the experience of companies from developed market economies. Nevertheless, these concepts provide us with a good methodological framework for surveying the strategies of companies from the transitional economies as well; some modification reflecting the peculiarities of transitional economies should just be made.